Interaction of the Srb10 Kinase with Sip4, a Transcriptional Activator of Gluconeogenic Genes in Saccharomyces cerevisiae - Vincent, Olivier (American Society for Microbiology, 2001)
Sip4 is a Zn(2)Cys(6) transcriptional activator that binds to the carbon source-responsive elements of gluconeogenic genes in Saccharomyces cerevisiae. The Snf1 protein kinase interacts with Sip4 and regulates its phosphorylation and activator function in response to glucose limitation; however, evidence suggested that another kinase also regulates Sip4. Here we examine the role of the Srb10 kinase, a component of the RNA polymerase II holoenzyme that has been primarily implicated in transcriptional repression but also positively regulates Gal4. We show that Srb10 is required for phosphorylation of Sip4 during growth in nonfermentable carbon sources and that the catalytic activity of Srb10 stimulates the ability of LexA-Sip4 to activate transcription of a reporter. Srb10 and Sip4 coimmunoprecipitate from cell extracts and interact in two-hybrid assays, suggesting that Srb10 regulates Sip4 directly. We also present evidence that the Srb10 and Snf1 kinases interact with different regions of Sip4. These findings support the view that the Srb10 kinase not only plays negative roles in transcriptional control but also has broad positive roles during growth in carbon sources other than glucose.